The Effect of Implementing an Independent Curriculum on Children's Critical and Creative Thinking Skills Through the Mediating Role of Technology Support in Early Childhood Education Institutions - Masitah, Widya; Sitepu, Juli Maini; Raniyah, Qaulan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze the effect of implementing the Independent Curriculum on the critical and creative thinking skills of early childhood students, with technology as a mediating variable, in Early Childhood Education (PAUD) institutions in Medan City. The research approach uses a quantitative, explanatory design. The population in this study was four early childhood education institutions included in the driving schools. The sampling technique was a census, with the entire population sampled, totaling 125 people. Data were collected through a structured questionnaire and analyzed using analysis models tracked with the SmartPLS software. The study's results indicate that implementing the Independent Curriculum has a positive, significant effect on children's critical and creative thinking skills. Technological support has been shown to significantly mediate the relationship between implementing the Independent Curriculum and improving children's critical and creative thinking skills. This study emphasizes the importance of integrating technology into the implementation of the Independent Curriculum to encourage the development of early childhood potential, especially in higher-order thinking. These findings provide practical implications for teachers, parents, and Early Childhood Education (PAUD) institutions in optimizing innovative learning strategies based on the Independent Curriculum with technological support.